2019
DOI: 10.1177/1533033819864313
|View full text |Cite
|
Sign up to set email alerts
|

PRDX4 and Its Roles in Various Cancers

Abstract: Reactive oxygen species play a vital role in cell survival by regulating physiological metabolism and signal transduction of cells. The imbalance of oxidant and antioxidant states induces oxidative stress within a cell. Redox regulation and oxidative stress are closely related to survival and proliferation of stem cells, cancer cells, and cancer stem cells. Peroxiredoxin 4, a typical endoplasmic reticulum-resident 2-Cys antioxidant of peroxiredoxins, can fine-tune hydrogen peroxide catabolism which affects cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 97 publications
0
25
0
Order By: Relevance
“…The latest study in hepatoblastoma (HB) indicated that PRDX4 promoted embryonal hepatoblastoma cell migration but induced fetal hepatoblastoma cell differentiation [ 18 ]. As different levels of reactive oxygen species (ROS), including H 2 O 2 , in tumor microenvironment exert specific effects on tumor [ 19 ], tumor microenvironment may also affect the role of PRDX4 in tumor via the crosstalk between PRDX4 and oxidative stress. In summary, PRDX4 plays different roles in different tumor contexts, including tumor histological type, tumor stage, and even tumor microenvironment, such as the oxidative stress balance.…”
Section: Introductionmentioning
confidence: 99%
“…The latest study in hepatoblastoma (HB) indicated that PRDX4 promoted embryonal hepatoblastoma cell migration but induced fetal hepatoblastoma cell differentiation [ 18 ]. As different levels of reactive oxygen species (ROS), including H 2 O 2 , in tumor microenvironment exert specific effects on tumor [ 19 ], tumor microenvironment may also affect the role of PRDX4 in tumor via the crosstalk between PRDX4 and oxidative stress. In summary, PRDX4 plays different roles in different tumor contexts, including tumor histological type, tumor stage, and even tumor microenvironment, such as the oxidative stress balance.…”
Section: Introductionmentioning
confidence: 99%
“…It regulates the activation of NF-kB by modulating IkB alpha phosphorylation. Recent studies have shown that it plays a key role in cancer progression across different types of cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of personalized medicine is patient selection. PRDX4 is overexpressed in diseases like prostate cancer, lung cancer, colorectal cancer, breast cancer, ovarian cancer, and lymph node metastases from oral cavity squamous cell carcinoma ( 57 ) and is associated with poor outcome in early-stage lung squamous cell carcinoma ( 58 ). Here, we showed that PRDX4 expression is associated with aggressive disease and that higher expression confers poor outcome in resectable pancreatic cancer (fig.…”
Section: Discussionmentioning
confidence: 99%